Inhibitory Effect of Termite Mound Soil Leachates on Some Human-Wildlife Pathogens (2021)
Although, there are reports of soil ingestion by wildlife (geophagy), but reasons for action remained elusive. A predominant hypothesis posits geophagy as source of medication for wildlife. This hypothesis albeit tested on different soils, but has sparsely been documented for termite mound soil (TMS). This study compared antibacterial susceptibility of aqueous leachates of four geophagic TMS1-4 from different sources with controls; a composite sample of forest soil (C1) and an aqueous solution of streptomycin sulphate (C2), against predominant human-wildlife pathogens; Staphylococcus aureus (S. aureus), Escherichia coli(E. coli) and Salmonella typhi (S. typhi). All TMS1-4 and C1-2 exhibited range of 1.33±0.58 to 8.25±2.87 inhibition zones (IZ) against all tested pathogens. While TMS2 (5.00±1.00) and C2 (5.00±1.00) gave similar IZ against S. typhi, C2showed significant highest IZ (8.25±2.87) againstE. coli. The exhibition of IZ in all TMS supports medication hypothesis. Hence, wildlife of the study area may be consuming TMSs for self-medication. Further studies may be needed to investigate properties of TMS responsible for exhibition of IZ.